2016
DOI: 10.3390/polym8050169
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cryomilling CNTs on the Thermal and Electrical Properties of CNT/PMMA Composites

Abstract: Abstract:In this study, the cryomilling of carbon nanotubes (CNTs) was carried out to accomplish better dispersion without using any hazardous chemicals. Accordingly, different samples of CNTs were prepared by varying the milling speed (10, 20, and 25 Hz) and time (5, 10, and 15 min) and incorporated into the poly(methyl methacrylate) (PMMA) matrix. The changes of the morphology were analyzed by utilizing a field emission scanning electron microscope (FESEM) and a high-resolution transmission electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The TGA pattern of neat PSA shows two-steps while other samples have a three-steps degradation pattern. These two steps of degradation in neat PSA are ascribed to the degradation of polymer chains (at around 290 °C) and total decomposition of the polymer (at around 370 °C) in PSA, respectively [20]. In all the AlN reinforced PSA composites, one extra step at around 100 °C, ascribed to the adsorbed moisture on AlN particles due to their hygroscopic nature, is also observed.…”
Section: Thermal Propertiesmentioning
confidence: 83%
“…The TGA pattern of neat PSA shows two-steps while other samples have a three-steps degradation pattern. These two steps of degradation in neat PSA are ascribed to the degradation of polymer chains (at around 290 °C) and total decomposition of the polymer (at around 370 °C) in PSA, respectively [20]. In all the AlN reinforced PSA composites, one extra step at around 100 °C, ascribed to the adsorbed moisture on AlN particles due to their hygroscopic nature, is also observed.…”
Section: Thermal Propertiesmentioning
confidence: 83%
“…34 It should be observed that the thermal property of the P(M-M)/CNTs-d microspheres is improved much less compared with that of P(M-M)/CNTs-6. This thermal stabilization effect is mostly due to that CNTs improve thermal stability by restricting the mobility of the polymer chains and acting as heat barriers.…”
Section: Molecular Weight and Pdi Of Pmma Copolymer And Polymer Extrmentioning
confidence: 92%
“…This thermal stabilization effect is mostly due to that CNTs improve thermal stability by restricting the mobility of the polymer chains and acting as heat barriers. 34 It should be observed that the thermal property of the P(M-M)/CNTs-d microspheres is improved much less compared with that of P(M-M)/CNTs-6. The thermal property is affected by the carbon nanofillers structure quality within the matrix, restricted mobility of the polymer chains, dispersion of nanofillers, and the interfacial adhesion between nanofillers and the polymer matrix.…”
Section: Molecular Weight and Pdi Of Pmma Copolymer And Polymer Extrmentioning
confidence: 92%
“…It is widely recognized that the mechanism of epitaxial crystallization is based on some certain crystallographic matches [1], and the mismatching of the contact lattice planes between the substrate and polymers cannot exceed 15%. For example; one-dimensional or two-dimensional lattice matches generate special interactions between the polymer chains and the substrate in the contacting interface which can alter not only the crystal structure and morphology of polymers, but the crystallization kinetics [2][3][4][5][6]. One-dimensional carbon nanotubes (CNTs) and two-dimensional graphene are frequently used as substrates to induce polymer crystallization because of their high surface area.…”
Section: Introductionmentioning
confidence: 99%